(untitled) (Journal of the College of Basic Education, 2023)
The current research aimed to identify the intellectual humility among the students of the Kindergarten Department and to identify the engagement among the students of the Kindergarten Department, and to know the correlation between intellectual humility and engagement among the students of the Kindergarten Department The research sample consisted of (400) female students from the Kindergarten Department for the academic year 2021-2022, and the researcher adopted a measure of intellectual humility and a measure of preoccupation, and applied the two measures to female students in the Kindergarten Department, then processed the data using Pearson’s correlation coefficient to find the coefficient of stability and relationship The relationship between intellectual humility and engagement among kindergarten students The researcher also used the t-test for one sample to find the significance of the difference between the arithmetic mean and the sample mean for the two variables. The results of the research reached the following: - 1 Kindergarten students have intellectual Humility. - 2 Kindergarten students have engagement. - 3 There is a positive correlation between intellectual humility and engagement with kindergarten students.